Imprisoned in English the hazards of English as a default language - Wierzbicka, Anna (Oxford University Press, 2014)
In Imprisoned in English, Anna Wierzbiçka argues that in the present English-dominated world, millions of people-including academics, lawyers, diplomats, and writers-can become "prisoners of English", unable to think outside English. In particular, social sciences and the humanities are now increasingly locked in a conceptual framework grounded in English. To most scholars in these fields, treating English as a default language seems a natural thing to do. The book's approach is interdisciplinary, and its themes range over areas of central interest to anthropology, psychology, and sociology, among others. Thelinguistic material is drawn from languages of America, Australia, the Pacific, South-East Asia and Europe. Wierzbicka argues that it is time for human sciences to take advantage of English as a global lingua franca while at the same time transcending the limitations of the historically-shaped conceptual vocabulary of English. And she shows how this can be done.